Pelatihan Keterampilan Kewirausahaan Terhadap Anak Sekolah Dasar di Kelurahan Sukorejo Melalui Pembuatan Gelang Manik - Ahmad Agung Setya Budi; Maulia Kusuma Wardhani; Fadilla Amarani Shola; Eka Vasia Anggis (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Education becomes a crutch in the lives of individuals and countries. Apart from transferring knowledge to other individuals, education also includes the development of character, attitudes and skills. One of the skills that today needs to be developed is entrepreneurial skills. Entrepreneurship education needs to be instilled in every individual as early as possible. This article will focus on a discussion regarding providing entrepreneurship training to children in Sukorejo Village, as an effort to instill an entrepreneurial spirit in children. The training methods provided include providing training facilities in the form of equipment and materials, demonstrations on making bracelets from beads, and mentoring. The results of this training can provide children with an understanding regarding the importance of entrepreneurial awareness and can foster an entrepreneurial spirit in children in Sukorejo Village